Sustained attention and associated memory and other cognitive failures in the young and able elderly - Porter, Nicola (Trinity College (Dublin, Ireland). School of Psychology, 2004)
The main aim of this thesis was to study how people pay attention over time and how this capacity changes with age. The populations under study were therefore the young and the able elderly and samples from these populations took part in a series of experiments to determine the differences between them in regard to sustained attention and related memory and other cognitive failures. Given that the population throughout the developed world is ageing rapidly, cognitive problems encountered by the elderly are becoming increasingly important areas of research.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin